Inequalities and age-period-cohort effects of global and regional burden for interstitial lung disease and pulmonary sarcoidosis: based on Global Burden of Disease study 2021 - Zhang, Lei; Wu, Yixian; Zhang, Jiarui; Qiu, Junxiong; Xiao, Yipu; Chen, Zhuochen; Zhang, Yanwei; Han, Jingjun (Frontiers in Medicine, 2025)
BackgroundInterstitial lung disease (ILD) and pulmonary sarcoidosis pose significant disease burdens on a global scale.MethodsThe underlying data was derived from the Global Burden of Disease (GBD) 2021 database. The disease burden was quantified through age-standardized rates (ASRs) and numbers of disability-adjusted life years (DALYs), prevalence, and incidence. The indicators' dynamic trends are captured through Joinpoint analysis and its average annual percentage change (AAPC). Concentration Index (CI) and Slope Index (SI) were employed to characterize the imbalances in the global disease burden. The age-period-cohort model was utilized to elucidate temporal trends in sociobiological factors on the disease burden.ResultsBetween 1992 and 2021, the ASRs of ILD and pulmonary sarcoidosis have increased globally. For another, the imbalanced distribution of disease burden increased, with more pronounced in high socio-demographic index (SDI) regions. Besides, age-standardized DALY rates (ASDRs) for ILD and pulmonary sarcoidosis were positively associated with age and period effects worldwide and complexly associated with cohort effects, increasing between 1882 and 1928 birthed cohorts and reducing after 1982. However, the distinct period-effect and cohort-effect curves observed in Africa which illustrate a negative correlation trend are noteworthy.ConclusionBetween 1992 and 2021, the global burden of ILD and pulmonary sarcoidosis increased, which were higher in high SDI countries and among the elderly. Furthermore, the disease burden increased with age and period and decreased for those born after 1982. However, the risk ratios of disease in Africa were negative with period-effect and cohort-effects, deserving effective interventions.